2004
DOI: 10.1256/qj.03.26
|View full text |Cite
|
Sign up to set email alerts
|

Properties and first application of an error‐statistics tuning method in variational assimilation

Abstract: SUMMARYThe method for tuning observational or background error statistics is presented and some of its properties are exposed using theoretical considerations and experiments carried out in a simplified framework. In particular, the method is shown to be equivalent to a maximum-likelihood evaluation and its efficiency is seen to depend on the number of observations. The results of several experiments carried out with the variational assimilation system of the French numerical weather-prediction system ARPEGE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 14 publications
(10 reference statements)
3
104
0
Order By: Relevance
“…The method could, in principle, provide guidance for any assimilation system. By considering the observation space subdomain [25], proper scaling, local averaging [26], or other methods discussed in Janjic et al [12] it may also be possible to extend this methodology to spatially varying error statistics. Based on our verification results in Part I [5], we found that there is a dependence between model values and error variances, which we will investigate further in view of our next operational implementation of the Canadian surface air quality analysis and assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…The method could, in principle, provide guidance for any assimilation system. By considering the observation space subdomain [25], proper scaling, local averaging [26], or other methods discussed in Janjic et al [12] it may also be possible to extend this methodology to spatially varying error statistics. Based on our verification results in Part I [5], we found that there is a dependence between model values and error variances, which we will investigate further in view of our next operational implementation of the Canadian surface air quality analysis and assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…In Berchet et al (2015), we proposed a general method in order to objectively quantify most of the critical sources of errors in the inversion. This improved algorithm is based on a Monte Carlo approach superimposed to maximum likelihood estimators (Chapnik et al, 2004;Michalak and Kitanidis, 2005).…”
Section: A Berchet Et Al: Ch 4 Flux In Eurasia 5395mentioning
confidence: 99%
“…The estimates σ 2 o may be interpreted as a first iteration of a fixed-point algorithm for tuning the observationerror variances (Desroziers et al, 2005) and their quality may be impaired by various factors including approximations entailed by nonlinearities in the observational operator and misrepresentation of the observationand background-error correlations (Chapnik et al, 2004;Ménard et al, 2009). An artificial adjustment of various input parameters in the DAS may be used to alleviate deficiencies in the specification of the observation-and background-error covariances.…”
Section: The Sensitivity Guidance For the Diagnosis Estimatesmentioning
confidence: 99%